Efeito do vidro bioativo S53P4 e laser no processo de reparo ósseo em calvária de ratas submetidas ao ácido zoledrônico - Bellato, Caio Peres (2018)
One of the adjunctive treatments for drug osteonecrosis is laser therapy. S53P4 bioactive glass based on silica with osteoconductive, antibacterial and angiogenic properties could also aid in its treatment. Thus, the objective of this study was to evaluate the bone repair process in surgically created critical defects in calvaria of rats submitted to zoledronic acid therapy, filled with S53P4 bioactive glass and low power laser application. Twenty - four adult rats (Rattus norvegicus albinus, Wistar) underwent surgical preparation of two defects in 5 - mm diameter pariet bones, divided into the following groups: AZC group - blood clot; Group AZL - blood clot with laser; Group AZBIO - bioactive glass; Group AZBIOL - bioactive glass with laser. Zoledronic acid was given in 5 doses of 0.035 mg / kg, with a two-week interval between them prior to surgery. After the periods of 14 and 28 days, the animals were euthanized. The data were submitted to statistical analysis with p <0.05. Regarding bone formation, at 14 days the groups AZBIO (52.15 ± 9.77) and AZBIOL (49.77 ± 13.58) showed higher values (p <0.001) compared to the AZC groups (23.35 ± 10, 15) and AZL (23.32 ± 8.75). In the 28-day period, there was a statistical difference (p = 0.048), with the AZBIO group (80.24 ± 5.41) being higher in relation to the AZC groups (59.59 ± 16.92) and AZL (45.25 ± 5,41). In the mononuclear cells, the AZBIOL group had the highest number (p = 0.048, p = 0.01) compared to the AZC group (15.6 ± 21.4, 5.5 ± 2.88) at 14 and 28 days. On the polymorphonuclear cells, at 14 days, the AZBIOL group (78.3 ± 60.1) presented high results (p = 0.048) compared to AZC (15.6 ± 21.4). Similarly to 28 days, the AZBIOL group (24.6 ± 12) also presented high results (p = 0.01) compared to AZC (5.5 ± 2.88). In the quantification of the blood vessels, at 28 days, there was a statistical difference (p = 0.003), with the AZL group being higher in relation to the other groups. The use of biomaterial and laser favored the process of bone repair in rats submitted to zoledronic acid therapy.